2017
DOI: 10.1371/journal.pone.0173044
|View full text |Cite
|
Sign up to set email alerts
|

Altered vasoreactivity in neonatal rats with pulmonary hypertension associated with bronchopulmonary dysplasia: Implication of both eNOS phosphorylation and calcium signaling

Abstract: Bronchopulmonary dysplasia (BPD) consists of an arrest of pulmonary vascular and alveolar growth, with persistent hypoplasia of the pulmonary microvasculature and alveolar simplification. In 25 to 40% of the cases, BPD is complicated by pulmonary hypertension (BPD-PH) that significantly increases the risk of morbidity. In vivo studies suggest that increased pulmonary vascular tone could contribute to late PH in BPD. Nevertheless, an alteration in vasoreactivity as well as the mechanisms involved remain to be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Consistent with these findings, the abundance of ET A receptors that mediate the effects of ET-1 on vascular tone was not altered, and α-SMA, a marker of remodeling of the pulmonary arteries associated with increased constriction, was not elevated. Other studies have shown that isolated pulmonary arteries from BPD rats exhibit increased vasoreactivity to U46619 (81) and in a 14 day BPD rat model increased vasoconstriction was associated with PH (82). It is possible that the absence of an increase in arterial α-SMA in hyperoxic pulmonary arteries in our mouse model could explain these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these findings, the abundance of ET A receptors that mediate the effects of ET-1 on vascular tone was not altered, and α-SMA, a marker of remodeling of the pulmonary arteries associated with increased constriction, was not elevated. Other studies have shown that isolated pulmonary arteries from BPD rats exhibit increased vasoreactivity to U46619 (81) and in a 14 day BPD rat model increased vasoconstriction was associated with PH (82). It is possible that the absence of an increase in arterial α-SMA in hyperoxic pulmonary arteries in our mouse model could explain these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…We (15) previously demonstrated that 5-HT is a potent vasoconstrictor in the developing lung. Recent studies reveal that intrapulmonary arteries isolated from rats with experimental PH/BPD demonstrate increased contractile response to 5-HT (19). Furthermore, pharmacological inhibition of 5-HT 2A-R activation decreases pulmonary vascular resistance in fetal sheep with experimental PH and protects against the development of experimental PH in mature rodents (16,29).…”
Section: Discussionmentioning
confidence: 99%
“…The development of overt pulmonary hypertension (PH) results in increased afterload to the right ventricle (RV), leading to RV hypertrophy (RVH) and ultimately failure, with high infant morbidity and mortality (Bhat et al, 2012 ). Rodent models of BPD, characterized by postnatal hyperoxia exposure, recapitulate many of the findings of human disease, including arrested alveolar and vascular development, PH and RV dysfunction (Goss et al, 2015 , 2017 ; Dumas de la Roque et al, 2017 ; Liang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 91%